Profile of Histone H3 Lysine 4 Trimethylation and the Effect of Lipopolysaccharide/Immune Complex-Activated Macrophages on Endotoxemia - Ruenjaiman, Vichaya; Butta, Patcharavadee; Leu, Yu-Wei; Pongpanich, Monnat; Leelahavanichkul, Asada; Kueanjinda, Patipark; Palaga, Tanapat (Frontiers in Immunology, 2020)
Macrophage plasticity is a process that allows macrophages to switch between two opposing phenotypes based on differential stimuli. Interferon γ (IFNγ)-primed macrophages stimulated with lipopolysaccharide (LPS) [M(IFNγ+LPS)] produce high levels of pro-inflammatory cytokines such as IL-12, TNFα, and IL-6 and low levels of the anti-inflammatory cytokine IL-10, while those stimulated with LPS in the presence of the immune complex (IC) [M(IFNγ+LPS+IC)] produce high levels of IL-10 and low levels of IL-12. In this study, we investigated the plasticity between M(IFNγ+LPS) and M(IFNγ+LPS+IC) in vitro and compared one of the active histone marks [histone H3 lysine 4 trimethylation (H3K4me3)] between M(IFNγ+LPS) and M(IFNγ+LPS+IC) using murine bone marrow-derived macrophages. We found that in an in vitro system, macrophages exhibited functional plasticity from M(LPS) to M(LPS+IC) upon repolarization after 2 days of washout period while IFNγ priming before LPS stimulation prevented this repolarization. Phosphorylation of p38, SAPK/JNK, and NF-κB p65 in M(LPS+IC) repolarized from M(LPS) was similar to that in M(LPS+IC) polarized from resting macrophages. To obtain the epigenetic profiles of M(IFNγ+LPS) and M(IFNγ+LPS+IC), the global enrichment of H3K4me3 was evaluated. M(IFNγ+LPS) and M(IFNγ+LPS+IC) displayed marked differences in genome-wide enrichment of H3K4me3. M(IFNγ+LPS+IC) showed increased global enrichment of H3K4me3, whereas M(IFNγ+LPS) showed decreased enrichment when compared to unstimulated macrophages. Furthermore, M(IFNγ+LPS+IC) exhibited high levels of H3K4me3 enrichment in all cis-regulatory elements. At the individual gene level, the results showed increased H3K4me3 enrichment in the promoters of known genes associated with M(IFNγ+LPS+IC), including Il10, Cxcl1, Csf3, and Il33, when compared with those of M(IFNγ+LPS). Finally, we investigated the impact of M(IFNγ+LPS+IC) on the systemic immune response by adoptive transfer of M(IFNγ+LPS+IC) in an LPS-induced endotoxemia model. The cytokine profile revealed that mice with adoptively transferred M(IFNγ+LPS+IC) had acutely reduced serum levels of the inflammatory cytokines IL-1β and IL-p12p70. This study highlights the importance of epigenetics in regulating macrophage activation and the functions of M(IFNγ+LPS+IC) that may influence macrophage plasticity and the potential therapeutic use of macrophage transfer in vivo.